Penentuan Sisa Umur Pakai Struktur Conveyor F pada Tambang Batubara PT GHI di Kabupaten Tapin, Provinsi Kalimantan Selatan - Rizqi Saefulfikri; Elfida Moralista; Zaenal (UNISBA Press, 2023)
Abstract. In the mining industry, there is a means of transportation for the process of moving mining materials, such as coal, by using a conveyor structure. The structure of the conveyor is made of steel so it is prone to corrosion by reacting with the environment. Corrosion can cause a loss that can result in a reduction in the thickness of the conveyor structure. Therefore, it is necessary to carry out control activities to monitoring in observations on the conveyor structure so that corrosion can be prevented. This study aims to determine the type of corrosion, corrosion rate, remaining service life, and control methods on the conveyor structure. The research methodology used is measuring the thickness reduction of the conveyor structure. The research was conducted on a conveyor structure with a length of 90 meters and 25 test points above ground level. The instrument used in measuring the thickness of the conveyor structure is Ultrasonic Thickness Gauge TT 130. The environmental conditions in the research area are air temperature in the range of 31oC - 37oC, while rainfall is in the range of 6.05 - 11.23 mm/year. The type of corrosion that occurs in this conveyor structure is uniform corrosion. The corrosion control method applied is the coating method with the primary coating using Seaguard 5000, the intermediate coating using Sherglass FF, and the top coating using aliphatic acrylic modified polyurethane. The corrosion rate on this conveyor structure ranges from 0.1828 - 0.3028 mm/year. This value is included in the good category based on the relative corrosion resistance of steel. The residual value of the conveyor structure's service life ranges from 7.19 to 9.65 years. Based on the calculation of the remaining service life of the conveyor structure at 25 test points, there are 24% which are estimated to not be able to reach the design life of 15 years. Abstrak. Dalam industri pertambangan terdapat alat transportasi untuk melakukan pemindahan material hasil penambangan yaitu dengan menggunakan struktur conveyor. Struktur conveyor terbuat dari baja yang rawan mengalami korosi dan beraksi dengan lingkungan. Korosi dapat menimbulkan suatu kerugian yang dapat mengakibatkan pengurangan ketebalan pada struktur conveyor. Oleh karena itu, perlu dilakukan kegiatan pengendalian hingga monitoring pada struktur conveyor agar mencegah korosi. Penelitian ini bertujuan untuk mengetahui jenis korosi, laju korosi, sisa umur pakai, dan metoda pengendalian pada struktur conveyor. Metodologi penelitian yang digunakan adalah pengukuran pengurangan ketebalan struktur conveyor. Penelitian dilakukan terhadap struktur conveyor dengan panjang 90 meter dan 25 test point. Alat yang digunakan dalam pengukuran ketebalan struktur conveyor yaitu Ultrasonic Thickness Gauge TT 130. Kondisi lingkungan di daerah penelitian yaitu temperatur udara kisaran 31oC - 37oC, sedangkan curah hujan kisaran 6,05 - 11,23 mm/tahun. Jenis korosi yang terjadi pada struktur conveyor ini yaitu korosi merata. Metode pengendalian korosi yang diaplikasikan adalah metode coating dengan primer coating menggunakan Seaguard 5000, intermediate coating menggunakan Sherglass FF, dan top coating menggunakan aliphatic acrylic modified polyurethane. Laju korosi pada struktur conveyor ini berkisar antara 0,1828 - 0,3028 mm/tahun. Nilai tersebut masuk ke dalam kategori good berdasarkan ketahanan korosi relatif baja. Nilai sisa umur pakai struktur conveyor yaitu 7,19 - 9,65 tahun. Berdasarkan dari perhitungan sisa umur pakai struktur conveyor pada 25 test point, terdapat sebesar 24% yang diperkirakan tidak dapat mencapai umur desain yaitu 15 tahun.